An evolutionary insight into the hatching strategies of pipefish and seahorse embryos. Issue 2 (14th March 2016) - Kawaguchi, Mari; Nakano, Yuko; Kawahara‐Miki, Ryouka; Inokuchi, Mayu; Yorifuji, Makiko; Okubo, Ryohei; Nagasawa, Tatsuki; Hiroi, Junya; Kono, Tomohiro; Kaneko, Toyoji
ABSTRACT: Syngnathiform fishes carry their eggs in a brood structure found in males. The brood structure differs from species to species: seahorses carry eggs within enclosed brood pouch, messmate pipefish carry eggs in the semi‐brood pouch, and alligator pipefish carry eggs in the egg compartment on abdomen. These egg protection strategies were established during syngnathiform evolution. In the present study, we compared the hatching mode of protected embryos of three species. Electron microscopic observations revealed that alligator pipefish and messmate pipefish egg envelopes were thicker than those of seahorses, suggesting that the seahorse produces a weaker envelope. Furthermore, molecular genetic analysis revealed that these two pipefishes possessed the egg envelope‐digesting enzymes, high choriolytic enzyme (HCE), and low choriolytic enzyme (LCE), as do many euteleosts. In seahorses, however, only HCE gene expression was detected. When searching the entire seahorse genome by high‐throughput DNA sequencing, we did not find a functional LCE gene and only a trace of the LCE gene exon was found, confirming that the seahorse LCE gene was pseudogenized during evolution. Finally, we estimated the size and number of hatching gland cells expressing hatching enzyme genes by whole‐mount in situ hybridization. The seahorse cells were the smallest of the three species, while they had the greatest number. These results suggest that the isolation of eggs from the external environment by paternal bearing might bring the egg envelope thin, and then, the hatching enzyme genes became pseudogenized. J. Exp. Zool. (Mol. Dev. Evol.) 9999B:XX–XX, 2016. © 2016 Wiley Periodicals, Inc.